A critical evaluation of the extent of disruption in the UK Financial Sector due to FinTech companies - Quoi, Oliver (2016)
The new wave of start-up Financial Technology, or FinTech, companies that have been heavily funded by Venture Capital firm has drawn much attention to them. Much intrigue and optimism has been attached to their power to change the modus operandi of the UK Financial Sector, particularly after the negative public perception of the industry after 2008. For some, these new companies represent hope and revolution, while for others they are a good business opportunity. Therefore, the purpose of this paper is to determine that extent of disruption that these FinTech companies are having on the UK financial sector and see if the hype is justified. The report focuses on seven sub-sectors of the UK Financial Sector, which are; Investing and Wealth, Management, Payments, Foreign Exchange, Currency, Lending, Current Accounts and Venture Capital. Firstly, a literature review of previous research on FinTech disruption in these sectors will be provided, then a quantitative and qualitative analysis and evaluation will be presented along with the most likely companies to cause disruption in regard the following criteria; Efficiency & Effectiveness of Processes, Improvement of Customer Interaction & Perception and Innovative Products Offered. Subsequently, conclusions and judgments will be drawn accompanied by a “disruption score” for each sub-sector and the UK financial sector as a whole. Ultimately, predictions on the future direction of FinTech disruption will be given. The key findings of the research are as follows. The subsector with the most disruption is Foreign Exchange, due to companies like TransferWise lowering the cost of making international payments. Contrarily, the subsector with the least amount of disruption is Currency due to the low adoption, high volatility and unfinished infrastructure of Bitcoin. Additionally, the rest of the sub-sectors are experiencing a spectrum of disruption, ranging from slight to strong disruption. To conclude, in totality, the UK Financial sector is experience substantial disruption from FinTech Companies.